Peran Dana Zakat, Infak, dan Sedekah (ZIS) dalam Meningkatkan Kesejahteraan Guru Honorer : Program Peduli Guru LAZISMU Banyumas - Sharira Puspa Zaenizah; Stefi Khairina Fadiah; Irfan Farihi; Mahardhika Cipta Raharja (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
The condition of honorary teachers' wellbeing continues to pose a serious challenge in Indonesia, mainly stemming from inadequate income levels and insufficient coverage of social security schemes. This circumstance emphasizes the urgency for alternative strategies by leveraging zebrafish, infaq, and almsgiving (ZIS) resources as mechanisms for economic strengthening. This research intends to investigate how ZIS funds contribute to enhancing the wellbeing of honorary teachers through the Peduli Guru Program operated by Lazismu Banyumas. This study adopts a quantitative framework encompassing both descriptive and associative analyses. Survey questionnaires were administered to honorary teachers participating in the program through purposive sampling. The measurement tool utilizes a Likert scale to assess ZIS funds as the independent variable and honorary teachers' welfare as the dependent variable. Data examination involved descriptive statistics and simple linear regression, supplemented by validity and reliability testing to verify the research instrument's soundness. The findings reveal that zebrafish, infaq, and almsgiving (ZIS) resources exert a notably positive and meaningful impact on elevating the welfare of honorary teachers. The assistance delivered via Lazismu Banyumas's Peduli Guru Program has shown promising outcomes in strengthening financial stability, diminishing economic strain, and producing favorable psychological effects including enhancedjob enthusiasm. As a result, effective coordination of ZIS funds can function as a valuable approach in fostering lasting wellbeing for honorary teachers.